2015
DOI: 10.1155/2015/640795
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy: A New Perspective in Asthma

Abstract: Takotsubo cardiomyopathy (TCM) is an entity of reversible cardiomyopathy known for its association with physical or emotional stress and may mimic myocardial infarction. We report an exceedingly rare case of albuterol-induced TCM with moderate asthma exacerbation. An interesting association that may help in understanding the etiology of TCM in the asthmatic population. Although the prognosis of TCM is excellent, it is crucial to recognize beta agonists as a potential stressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other studies have also shown stress cardiomyopathy in the setting of an acute asthma exacerbation or after repeated use of beta2-agonist inhalation [10][11][12][13][14][15][16][17]. Most of the cases involved elderly women with a history of asthma presenting with dyspnea rather than chest pain [12][13][14][15][16][17][18][19]. Only 1 case involved a male patient who presented with asthma exacerbation complicated with stress cardiomyopathy after frequent inhalation of steroids and long acting beta2-agonist [17].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown stress cardiomyopathy in the setting of an acute asthma exacerbation or after repeated use of beta2-agonist inhalation [10][11][12][13][14][15][16][17]. Most of the cases involved elderly women with a history of asthma presenting with dyspnea rather than chest pain [12][13][14][15][16][17][18][19]. Only 1 case involved a male patient who presented with asthma exacerbation complicated with stress cardiomyopathy after frequent inhalation of steroids and long acting beta2-agonist [17].…”
Section: Discussionmentioning
confidence: 99%
“…Parodi et al reported an estimated prevalence of LBBB in 9% of TTC patients at the time of diagnosis [28]. Other isolated case reports establishing an association between TTC and new or old LBBB have also been reported in the literature [2931]. The presence of conduction abnormalities in TTC can be attributed to decreased blood flow to the ventricular conduction system either due to left ventricular dyskinesia or catecholamine-induced vasospasm [30].…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest the study by Marmoush et al [ 1 ] about the 80-year-old woman with an exacerbation of her asthma who suffered Takotsubo syndrome (TTS), after using “her rescue albuterol inhaler several times.” As the authors state this is not the first case of an albuterol-triggered TTS, as shown by many similar cases of TTS published as single case reports and series of patients derived from cohorts admitted to the respiratory intensive care unit, treated with a variety of β 2 -adrenergic agents. I have some thoughts for the authors to consider.…”
mentioning
confidence: 99%